2017
DOI: 10.1186/s12974-017-0862-1
|View full text |Cite
|
Sign up to set email alerts
|

Lack of interleukin-13 receptor α1 delays the loss of dopaminergic neurons during chronic stress

Abstract: BackgroundThe majority of Parkinson’s disease (PD) cases are sporadic and idiopathic suggesting that this neurodegenerative disorder is the result of both environmental and genetic factors. Stress and neuroinflammation are among the factors being investigated for their possible contributions to PD. Experiments in rodents showed that severe chronic stress can reduce the number of dopaminergic neurons in the substantia nigra pars compacta (SNc); the same cells that are lost in PD. These actions are at least in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…Interesting new research also finds that IL-4 and IL-13 may play roles in learning and memory [29,30], suggesting a role for neurons in IL-4 and IL-13 signaling. Furthermore, a novel role for neuronal IL-13Rα1 was recently discovered, in which stimulation of this receptor led to dopaminergic cell loss [28]. In our study, we confirmed that SH-SY5Y IL-4 and IL-13 signaling is enhanced following ethanol treatment in BV2/SH-SY5Y microglial co-cultures, with an increased induction of IL-4R and IL-13R by ethanol in co-cultured SH-SY5Y.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Interesting new research also finds that IL-4 and IL-13 may play roles in learning and memory [29,30], suggesting a role for neurons in IL-4 and IL-13 signaling. Furthermore, a novel role for neuronal IL-13Rα1 was recently discovered, in which stimulation of this receptor led to dopaminergic cell loss [28]. In our study, we confirmed that SH-SY5Y IL-4 and IL-13 signaling is enhanced following ethanol treatment in BV2/SH-SY5Y microglial co-cultures, with an increased induction of IL-4R and IL-13R by ethanol in co-cultured SH-SY5Y.…”
Section: Discussionsupporting
confidence: 86%
“…In brain, microglia appear to express low levels of IL-4 and IL-13 basally but can induce expression under certain conditions [26,27]. Interestingly, IL-13 receptor is located on dopaminergic neurons and overactivation of this receptor has been linked to loss of dopaminergic cells [28], prompting studies on the impact of alcohol exposure due to the importance of dopamine for drug-induced reward. Furthermore, IL-4 and IL-13 also have roles in learning and memory [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…We sought to determine how widespread microglial activation might be in brain following alcohol exposure. The specific brain regions were selected based on our previous studies demonstrating that these brain areas are important in neuroimmune functions as well as sensitive to the effects of alcohol (Alboni et al, ; Amodeo et al, ; Ehlers et al, ; Ehlers et al, ; Ehlers et al, ; Hwang et al, ; Mori et al, ; Mori et al, ; Morrison et al, ; Sugama et al, ; Sugama et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous study demonstrated that IL13Rα1 regulates the cellular responses to various stressful stimulations that it could promote more fibrosis in response to transforming growth factor-β (TGF-β) [28]. Likewise, neuronal IL13Rα1 increases the susceptibility to oxidative damage [29]. In this study, our loss-and gain-of functional experiments argued IL13Rα1-mediated signaling pathway as a novel molecular program to counter the apoptotic resistance of RA FLSs towards ER stress.…”
Section: Discussionmentioning
confidence: 58%